Foyle's war. Set 7 [videorecording (DVD)] - Horowitz, Anthony, 1955-; Hay, Andy, 1954-; Orme, Stuart; Kitchen, Michael, 1948-; McMullan, Tim; Weyman, Dan; Weeks, Honeysuckle, 1979- (Distributed by RLJ Entertainment, 2013)
As the enormously popular mystery series returns, World War II is over, but the Cold War simmers in 1946 London. DCS Christopher Foyle has retired from police work when Britain's secret intelligence service compels him to join its ranks. Reunited with his former colleague, newlywed Sam Wainwright, Foyle faces new-but no less deadly-threats in the world of spies and counterintelligence.